Efektivitas Edukasi Berbasis Video terhadap Pengetahuan, Sikap, dan Pencegahan Demam Berdarah pada Anak Sekolah: Tinjauan Sistematik - Fathariq, Ganar Rajni; Permatasari, Henny; Widyatuti; Rahmadiyah, Dwi Cahya (Universitas Hang Tuah Pekanbaru, 2025)
Dengue fever (DF) is a significant global health burden with steadily increasing incidence, especially in Indonesia, which reported 88.593 cases from January until May 2024. School-aged children constitute a key population, as the school environment effective setting for implementing prevention and control programs. This systematic review aims to compare the effectiveness of video-based education with conventional teaching methods in improving knowledge, attitudes, and preventive practices (KAP) related to dengue fever among school children. The review was conducted in accordance with the PRISMA 2020 guidelines, with searches performed across seven major databases between March and April 2025. Inclusion criteria were developed using the PICO framework, encompassing quantitative studies involving children aged 12–15 years who received video-based dengue prevention education. Seven studies met the criteria, comprising seven quasi-experimental designs, all of which were appraised using the JBI Critical Appraisal Checklist. The findings demonstrate that video-based educational interventions consistently improve children’s KAP regarding dengue prevention. These results provide an important foundation for community health nursing practice, highlighting the potential of video media as an effective educational tool in dengue prevention efforts. Future research should employ cluster RCT designs with extended follow-up periods and objective behavioral measurements to capture sustained behavioral change. The application of theoretical frameworks, such as the Health Promotion Model, should be emphasized to clarify the mechanisms underlying behavior change. Multisite studies that incorporate social support from teachers, parents, and peers are also needed to enhance the generalizability and sustainability of dengue prevention interventions.